Tetrandrine-induced downregulation of lncRNA NEAT1 inhibits rheumatoid arthritis progression through the STAT3/miR-17-5p pathway. (2nd November 2022) - Duan, Bo; Yu, Zhao; Liu, Ruilin; Li, Jigao; Song, Zhe; Zhou, Quan; Chen, Lichuan
Abstract: Background: The inhibitory effect of Tetrandrine (Tet) on rheumatoid arthritis (RA) is well established. However, its exact molecular mechanism remains unknown. Methods: RT-qPCR coupled with western blotting was employed to analyze the expression of NEAT1, miR-17-5p, and STAT3 in RA tissues and/or RA-fibroblast-like synoviocytes (RA-FLS) treated with 3 μmol/L of Tet for 48 h. Cell Counting Kit-8 assay and flow cytometry were performed to assess RA-FLS proliferation and apoptosis. Luciferase reporter assays were used to validate the interactions between miR-17-5p and STAT3 or NEAT1. Results: The expression of NEAT1 decreased in a time-dependent manner upon Tet treatment. Tet significantly inhibited RA-FLS proliferation and triggered apoptosis by downregulating NEAT1 expression. Additionally, NEAT1 directly targeted miR-17-5p to upregulate STAT3 expression. Tet-induced low NEAT1 expression impaired RA-FLS growth by targeting miR-17-5p and inhibiting STAT3. Conclusion: Tet exerts its inhibitory role in RA progression by regulating the NEAT1/miR-17-5p/STAT3 pathway.